Cognitive styles and the effects of stress from cognitive load and time pressures on judgemental decision making with learning simulations: Implications for HRD. (2016) - Workman, Michael
With the theory of mental self-government and cognitive styles to ground our study, we explored whether cognitive styles and stress affected decisions requiring subjective judgement. To carry out our study, we employed simulations in a dual task test under two conditions, the first condition was timed and cognitive-load induced, and the other was with the leisure of time without cognitive load. The novelty in our approach is that we used observations of decisions made from scenarios presented in the simulations, and we found that cognitive styles influenced decisions differently depending on condition. Our results have implications for human resource development, recruitment and placement, as well as for job-task assignment, assessment, and performance.